KONSUMSI PANGAN DAN GIZI SERTA SKOR POLA PANGAN HARAPAN (PPH) PADA ANAK USIA 2—6 TAHUN DI INDONESIA - Teguh Jati Prasetyo; Hardinsyah Hardinsyah; Tiurma Sinaga (Food and Nutrition Society of Indonesia, 2013)
This study aimed to assess food and nutrients intake, Nutrient Dietary Quality (NDQ), and Desirable Dietary Pattern (DDP) score of children aged 2—6 years.This study was carried out through analyzing a consumption data set of the National Basic Health Research (Riskesdas) 2010 were collected using 24 hour recall method. Total number 16 675 of children aged 2—6 years. The results showed that most children eat cereals (99.4%) and least eat oily seeds (1.6%). The children had deficiency of energy, fats, and water. They also had deficiency of calcium, vitamin A, vitamin B9, and vitamin C. The mean DDP score of the children was 67.1±12.9. The mean NDQ of the children was 62.4±17.1. Correlation between DDP score and each of NDQ was found 0.578—0.621 that showed moderate validity result.